2020
DOI: 10.1002/cyto.b.21874
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocytic variant of hypereosinophilic syndrome: A report of seven cases from a single institution

Abstract: Background: Lymphocytic variant of hypereosinophilic syndrome (L-HES) is a subtype of HES driven by cytokines produced by clonal T-cells. Due to the rarity of its occurrence and challenges in diagnosis, this subtype of HES is under recognized. Methods and Results: We report seven patients with L-HES, diagnosed from a group of 136 patients who were referred to our institution for the work-up of hypereosinophilia. The clinical presentation, symptoms and signs were heterogeneous and uncharacteristic; indistinguis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 30 publications
0
16
1
Order By: Relevance
“…In contrast, a significantly higher expression level was observed for CD2, CD45RO and CD95, appearing as a single tight histogram with high staining intensity on CD3 -CD4 + T cells, clearly demarcating these cells from the normal CD4 + cells in the same sample. Although we and others (13) commonly observe increased staining intensity for CD5 on these cells, the difference with CD3 + CD4 + cells was not statistically significant.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…In contrast, a significantly higher expression level was observed for CD2, CD45RO and CD95, appearing as a single tight histogram with high staining intensity on CD3 -CD4 + T cells, clearly demarcating these cells from the normal CD4 + cells in the same sample. Although we and others (13) commonly observe increased staining intensity for CD5 on these cells, the difference with CD3 + CD4 + cells was not statistically significant.…”
Section: Discussioncontrasting
confidence: 86%
“…Although L-HES is an indolent lymphoproliferative disorder, the large majority of patients have normal circulating lymphocyte counts (10,11,13). We recently reported that the abnormal CD3 -CD4 + T cell subset represented less than 2% of total lymphocytes in 40% of patients (10), explaining that these cells rarely impact differential counts.…”
Section: Discussionmentioning
confidence: 99%
“…This contrasts with more limited data that exists on the potential diagnostic utility of immunophenotyping in MPN, HES, or the altered proliferation profiles in these and other, myeloid neoplasms (Shameli et al, 2020;Ouyang et al, 2015;Herborg et al, 2018;Matarraz et al, 2012;Matarraz et al, 2011). In this issue of Cytometry B six original research papers and a case report have used flow cytometry to study MDS, MDS/MPN, MPN and HES (Shestakova et al, 2021;Davydova et al, 2021;Mestrum et al, 2021;Panda et al, 2021;Vijayasekharan et al, 2021;Hu et al, 2021;Espasa et al, 2021). In the first of these six papers, Shestakova et al (2021) explored the utility of automated leucocyte parameters including cell volume, conductivity and light scatter properties (VCS parameters) as assessed in an automated hematological analyzer, as a read-out for dysplastic MDSassociated features.…”
Section: Flow Cytometry In Myeloid Neoplasmsmentioning
confidence: 99%
“…In the following manuscript, Panda et al (2021) investigate mast cell differentiation of blast cells in patients with myeloid neoplasias not fulfilling diagnostic criteria for systemic mastocytosis or myelomastocytic leukemia (Swerdlow et al, 2017). Overall, 9 patients showed blasts with a CD117 hi CD34 het HLADR -/lo CD203c + immature mast cell-associated immunophenotype, supporting the potential existence a small percentage of underdiagnosed myelomastocytic leukemia cases; diagnosis of these nine patients corresponded to CML at any phase of the disease (n=4), to newly diagnosed and secondary AML (n=4) and to one chronic myelomonocytic leukemia, whose features are described in detail in the manuscript (Panda et al, 2021) Finally, the sixth manuscript on myeloid neoplasms reports on flow cytometry immunophenotypic findings in seven patients diagnosed with lymphocytic variant of HES, out of a series of 136 patients referred to a single institution for the diagnostic work-up of eosinophilia (Hu et al, 2021). In this report, Hu et al (2021) showed that flow cytometry immunophenotyping was critical (and complementary to molecular analyses) for systematic demonstration of aberrant CD3-CD7-/lo CD4+ CD5+ CD2+ CD8-T-cells associated with T cell clonality, in all seven patients.…”
Section: Flow Cytometry In Myeloid Neoplasmsmentioning
confidence: 99%
See 1 more Smart Citation